Femur open wedge corrective osteotomy and gradual deformity correction - Ang, Poh Thean Charles; Mohd Yusof, Nazri; Awang, Mohd Shukrimi; Wong, Kuok Joon Jonathan (American Journal of Biomedical Science & Research, 2019)
Deformity correction remains a challenge to treat. However, with the advancement of corrective osteotomy and illizarov external fixation, these complex deformities are better addressed. We report a case of atrophic non- union seen in a seventeen-year-old boy who was initially treated with locking plate following an open fracture to his left distal femur and tibial plateau. Infective causes was ruled out. Plain radiograph reveals a broken implant and atrophic non- union of his distal femur with thirty degrees medial angulation. He underwent removal of implant, corrective osteotomy and illizarov external fixation. At ten weeks post surgery, the deformity was completely corrected. The illizarov external fixator was removed at sixteen weeks post surgery, and he was able to ambulate without pain. Following a few sessions of physiotherapy over a period of three months, he was able to regain his knee full range of movement and was able to return to sports. Corrective osteotomy and illizarov external fixation remains the treatment of choice in chronic limb deformities, especially if suspicious of infection. This minimizes the risk of neurovascular tractional injury and implant related infection which will be disastrous to manage.